1986
DOI: 10.1177/014107688607900708
|View full text |Cite
|
Sign up to set email alerts
|

Familial Retrocaecal Appendicitis

Abstract: Four members of the same family operated on for acute retrocaecal appendicitis are reported. It is suggested that they provide further support for the hypothesis that an hereditary factor might be involved in the pathogenesis of acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Increased risks for appendicitis were described mainly as low-fibre diet (Burkitt 1971;Adamis et al 2000), infections due to edema causing obstruction of appendix lumen and hereditary (Andersson et al 1979). Familiar history of appendicitis is considered to be due a particular position of the appendix, which predisposes it to infection (Shperber et al 1986). However, irregular myenteric ganglia distribution with currently unknown relation to appendix position may also be hereditary.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risks for appendicitis were described mainly as low-fibre diet (Burkitt 1971;Adamis et al 2000), infections due to edema causing obstruction of appendix lumen and hereditary (Andersson et al 1979). Familiar history of appendicitis is considered to be due a particular position of the appendix, which predisposes it to infection (Shperber et al 1986). However, irregular myenteric ganglia distribution with currently unknown relation to appendix position may also be hereditary.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of such ac ongenital malformation alone is not sufficient to precipitateanattack of acute appendicitis, it could well be considered as apredisposing factor in that it presentsthe mechanism by which the lumen of the appendix could be obstructed. Various anomalies of the appendix, such as missing section of mesoappendixo rm orphological and anatomical variationsi ncluding ac oiled, short, longo rr etrocaecal appendix (15)(16)(17) described by many authors. Some authors also suggested that anatomical variations of the appendix might be inheritedasasimple dominant unit-character (15,17).…”
Section: Familyhistorymentioning
confidence: 99%
“…A retrocecal appendix is common and one series showed the appendix to be retrocolic and retrocecal in 58% of cases [1] . A retrocecal appendix has been described also in families and is thought to be inherited as a simple dominant unit character [11] . Studies of the fetal appendix, however, show that it is almost always subcycle during this period [12] .…”
Section: Discussionmentioning
confidence: 99%